Results of wildfowl ringing at Abberton Reservoir, Essex 1949 to 1966 - Wainwright, C B (Wildfowl, 1967)
Between 1949 and 31st July 1966, 37,924 ducks and 376 swans were ringed at Abberton Reservoir, yielding 8,162 recoveries so far. Teal made up 70% of the catch and Mallard 21%. Fourteen other duck species have also been marked. The seasonal variations in the catch are examined and an association is found between the catch of Teal and the mean of the monthly winter counts on the reservoir. Tabular summaries of the recoveries show marked differences between species in the proportions recovered locally and overseas. Teal have been reported from 35 countries. Mallard recoveries from within 30 miles of Abberton show that there has not been a falling off in the recovery rate due to 'reporter boredom.' Average adult mortality rates include Mallard 43%, Teal 45%, Garganey 47% and Gadwall 52%.